DANGEROUS PRODUCTS FOR ANIMALS. ONION AND GARLIC POISONING OF DOGS AND CATS - Paslawski, R.; Paslawska, U.; Sorokova, S. (Scientific Progress & Innovations, 2021)
The most popular pets – dogs and cats – are now considered members enjoying full rights of most families around the world. They are sociable animals, they get along well with both adults and children, and they are always happy with their master and express their love for him (her) in every way. It is believed that dogs and cats are not very fastidious about food products, and sometimes cases can be observed when animals eat non-typical food. So sometimes dogs taste sweets and chocolates and cats try pickled cucumbers and chips. Of course, such diet has a negative effect on the body of pets, and even when at first sight it remains unnoticeable. It should be mentioned that in most cases, food poisoning in animals is the consequence of the absence or lack of information from owners about the peculiarities of feeding their pets. At present, there are more and more cases of visits to veterinary doctors in the world with cases of dogs and cats’ poisoning with various food products, including onion (Allium cepa L.) and garlic (Allium sativum L.). Despite the usefulness of these plants to humans, they are still toxic to dogs and cats due to the presence of such substances as sulfoxides and sulfides in their composition, especially allyl and propyl di-, tri- and tetra-sulfides contained in onion, and allicin (diallyl disulfide-S-oxide) and ajoena (2-propenyl-3 [3- (2-propenylsulfinyl) -1-propenyl] disulfide), which garlic contains. Very often cases of poisoning are registered among pet owners who like to feed their animals “from the table”, i.e. the same products that they eat themselves. Therefore, the purpose of this review was to characterize the toxic properties of onion and garlic, to detect the changes that occur in the body of animals when eating these vegetables, and briefly outline the basic principles of treatment manipulation at poisoning. The disclosure of such aspects will enable veterinary doctors to gain additional knowledge in this area, which in turn will allow diagnose correctly the pathology, described above and, accordingly, to carry out treatment measures if necessary. It should be kept in mind that the information provided in this review will be useful not only for veterinary experts but also for owners of dogs and cats, as it will give some understanding of the peculiarities of feeding their pets.